Literature Review: Efektivitas Kurikulum Merdeka Dalam Meningkatkan Kemandirian Belajar Peserta Didik - Lubis, Adelia Marta; Sinaga, Erickson; Simbolon, Legi Likasri; Aulia, Nazwa; Munthe, Raja Parnaungan (CV. ULIL ALBAB CORP, 2026)
The Independent Curriculum is an educational policy designed to provide learning flexibility, differentiation, and student-centered learning experiences. However, its effectiveness in fostering independent learning still shows mixed results across educational units. This study aims to analyze the effectiveness of the Independent Curriculum in enhancing student learning independence through a literature review approach. Data were collected from scientific articles indexed by Google Scholar, DOAJ, and the Garuda Portal with keywords related to